2023
DOI: 10.2320/matertrans.mt-m2022124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium Dioxide on Aggregation of Reduced Metallic Iron in Molten Slag

Abstract: The reduction process of lunar regolith simulant was designed to obtain metallic iron (Fe) and utilize lunar resources, focusing mainly on the effect of titanium dioxide (TiO 2 ) on the recovery of metallic Fe from molten slag. Thermodynamic calculations were conducted to predict the equilibrium phases existing at high temperature upon heating the regolith simulant to 1600°C under an oxygen partial pressure of 10 ¹15 atm, in which the metallic Fe coexisted with the molten slag. Based on these predictions, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…TiO 2 is known to lower the viscosity of molten silicate-based slag 16) , which is generally advantageous for metal recovery. However, our previous study 15) showed that recovery of the Fe alloy decreased with addition of TiO 2 in the slag, even though the viscosity of the molten slag decreased. We concluded that when the molten slag wetted the liquid Fe, a repulsive capillary force acted on the contact points between Fe particles in the slag 15,17) , making it difficult for the fine liquid Fe particles to coalesce.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…TiO 2 is known to lower the viscosity of molten silicate-based slag 16) , which is generally advantageous for metal recovery. However, our previous study 15) showed that recovery of the Fe alloy decreased with addition of TiO 2 in the slag, even though the viscosity of the molten slag decreased. We concluded that when the molten slag wetted the liquid Fe, a repulsive capillary force acted on the contact points between Fe particles in the slag 15,17) , making it difficult for the fine liquid Fe particles to coalesce.…”
Section: Introductionmentioning
confidence: 81%
“…The lunar regolith simulant was the same as that used in our previous study 15) . The regolith simulant was crushed to less than 125 µm, dried at 473 K for 24 h to remove moisture, and then uniformly mixed with various oxides: ilmenite, albite, and Na 2 O•xSiO 2 compounds.…”
Section: Experimental 21 Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations